Parents and Students' Response to Distance Learning (Google Classroom) - Novida Renoningtyas; Erna Risfaula Kusumawati (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2021)
This study aims to determine the response of parents and primary students to distance learning based on google classroom during the Covid-19 pandemic. The method used in this study is a qualitative method with data collection in the form of interviews, documentation, and observation. The results showed that both students and their parents objected to using google classroom as a learning media for distance learning activities. According to their explanation, the use of Google Classroom requires strong network access to open or send assignments, besides that data packets also run out quickly due to the use of this distance learning application. For students and parents who have difficulty, an alternative to overcome this is to send assignments via WhatsApp to the teacher concerned.